The Role of Trust in Corporate Social Responsibility and Worker Relationships - Gaudêncio, Pedro (2018)
Purpose – The study aims to show how organizational Corporate Social Responsibility (CSR) can influence workers’ attitudes and behaviors, especially in terms of affective commitment (AC), job satisfaction (JS) and turnover intention (TI). A second aim is to explore the social exchange process that may underlie this relationship, by examining the mediating role of Organizational Trust (OT). Design/methodology/approach – The authors employ structural equation modelling based on survey data obtained from 315 Portuguese individuals. Findings – The findings show that perceptions of CSR predict workers’ attitudes and behaviors directly through the mediating role of OT. They suggest that managers should implement CSR practices because these can contribute towards fostering OT, improving workers’ AC and JS, and reducing TI. Originality/value – This study enriches the existing knowledge about social exchange relationships in organizational contexts, and responds to the need to understand underlying mechanisms linking CSR with workers’ organizational outcomes, by analyzing CSR practices in a holistic stakeholder perspective.